‘Mastermind’ English board game / Alya Fatihah Asri and Mahdalela Rahim - Asri, Alya Fatihah; Rahim, Mahdalela (Academy of Language Studies, 2023)
As the English language is normally taught through schools and books, it does not motivate people to enjoy the process of learning the language. In order to make the process of learning enjoyable, this research has been conducted to uncover the ability of a board game named Mastermind as a supplementary medium to learn English among people. The main objective for is to identify the potential of this game as fun and enjoyable platform of learning language. It is also hoped to motivate people to engage with English Language while playing. Through the board game, players are challenged with 100 random questions from different categories; grammar, science, riddle, translation and general knowledge. These questions were all written in English language. They do not only test the players’ basic grammar knowledge but also their critical thinking, communication and translation skills. The game was played by 14 players between 18-22 years old. The findings of the survey revealed that the ‘Mastermind’ board game received positive feedback from the respondents and playing the game helped them increase their engagement in the English Language.